Immunity to error through misidentification and the functionalist, self-reflexive account of episodic memory - James, Steven (Estudios de Filosofía, 2021)
Fernández (2019) offers an account of the nature of episodic memory that marries two core ideas: (i) role-functionalism about episodic memory, and (ii) self-reflexive mnemonic content. One payoff of this view is that episodic memory judgments are immune to error through misidentification. Fernández takes this to reveal something important about the nature of one’s self-awareness in memory and our first-person conception of ourselves. However, once one sees why such judgments are immune in this way, according to the proposed account, the fact that they are immune becomes moot. While technically immune to error through misidentification, episodic memory judgments are not grounded in a way such that they have any interesting epistemological import for the subject (in contrast to other paradigms of such judgments), and any insights about our self-awareness and self-conception are directly derivable from the metaphysics of memory content alone.